A vibration amplitude model for the giant magnetostrictive ultrasonic processing system. (March 2018) - Cai, Wanchong; Zhang, Jianfu; Yu, Dingwen; Feng, Pingfa; Wang, Jianjian
For the purposes of estimation and control of the vibration amplitude in rotary ultrasonic machining, the relation between vibration amplitude and excitation signal was examined. The mechanical components outside the Terfenol-D were regarded as a single-degree-of-freedom mass spring damping system, and an equivalent mechanical model of the giant magnetostrictive ultrasonic processing system was addressed. After that, the vibration amplitude was modeled as a function of the frequency and amplitude of the excitation current by considering both magnetization and magnetostriction of Terfenol-D and ultimately achieved through parameter identification using the methods of impedance analysis and nonlinear least-squares fitting. In addition, the relation between resonant frequency of the giant magnetostrictive ultrasonic processing system and the magnitude of the excitation current was studied so that the vibration amplitude model was improved. Thus, the vibration amplitude of the giant magnetostrictive ultrasonic processing system excited by various electric signals with different frequencies and amplitudes can be calculated. As demonstrated by comparison with experimental results, the vibration amplitude model can accurately estimate the vibration amplitude of the giant magnetostrictive ultrasonic processing system. It indicates that the model is meaningful for the design and control of the giant magnetostrictive ultrasonic processing system.